Aspect-oriented modeling framework for security hardening. (March 2016) - Mouheb, D.; Alhadidi, D.; Nouh, M.; Debbabi, M.; Wang, L.; Pourzandi, M.
Abstract Aspect-oriented modeling (AOM) emerged as a promising paradigm for handling crosscutting concerns, such as security, at the software modeling level. Most existing AOM contributions are presented from a practical perspective and lack formal syntax and semantics. In this paper, we present a practical and formal AOM framework for software security hardening. Our contributions are threefold. First, we define an AOM approach for the specification of security aspects at the unified modeling language (UML) design level. Second, we design and implement the matching and the weaving processes into UML design models. Third, we elaborate formal specifications for aspect matching and weaving in UML activity diagrams. Finally, we demonstrate the viability and the relevance of our propositions using a case study. The proposed framework is supported by a tool built on top of IBM-Rational Software Modeler.